2005
DOI: 10.1007/s11177-005-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

RAPD and ISSR analyses of regenerated pea Pisum sativum l. plants

Abstract: Long-term pea callus cultures of different genotypes (mutants R-9 and W-1 and cultivar Viola) were used to regenerate plants (generation R 0 ). The regenerants displayed changes both in qualitative and in quantitative traits. The most dramatic morphological alterations and complete sterility were observed in regenerants of the cultivar Viola. To estimate the genetic differences, regenerants were compared with the original lines with the use of RAPD (random amplified polymorphic DNA) and ISSR (inter simple sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…two of 5 superior somaclones showing two fold increase in total oil content showed gross changes in RAPD banding pattern. Kuznetsova et al (8) analysed regenerants of long-term callus cultures of different pea genotypes (R-9, W-1 and cultivar Viola). Regenerants displayed changes both in qualitative and in quantitative traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…two of 5 superior somaclones showing two fold increase in total oil content showed gross changes in RAPD banding pattern. Kuznetsova et al (8) analysed regenerants of long-term callus cultures of different pea genotypes (R-9, W-1 and cultivar Viola). Regenerants displayed changes both in qualitative and in quantitative traits.…”
Section: Resultsmentioning
confidence: 99%
“…it involves amplification of genomic DNA with short and random primers at low annealing temperatures (22). this technique is employed by many researchers in genetic screening of plant tissue cultures and regenerants (8,12). cReD-RA "coupled Restriction Enzyme Digestion-Random Amplification" is a method to detect DnA methylation, which is one of the main causes of epigenetic variations (2).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the RAPD technique has been applied to assess genetic diversity in pea (Simioniuc et al 2002), green gram (Karuppanapandian et al 2006a), cow pea (Karuppanapandian et al 2006b), and black gram (Karuppanapandian et al 2007). The ISSR technique has been used to examine genetic relationships in genus Vigna (Souframanien and Gopalakrishna 2004) and several other crops (Awasthi et al 2004;Kuras et al 2004;Kuznetsova et al 2005;Thimmappaiah et al 2009). In black gram varieties, ISSR markers amplified polymorphic bands more efficiently than RAPD markers (77.8 compared with 66.5%, respectively; Table 3) and similar results have been obtained for several other crops, including wheat (Nagoaka and Ogihara 1997) and groundnut (Raina (Table 3).…”
Section: Rapd and Issr Comparisonmentioning
confidence: 99%
“…Moreover, Kuznetsova et al (2005) showed their reliability in analysing DNA polymorphisms generated by long-term culture and subsequent regeneration in pea. In our study, the same molecular markers were also shown to be efficient in determining the genetic changes induced by tissue culture and by artificial DNA demethylation.…”
Section: Discussionmentioning
confidence: 99%